Positive Solutions of Fractional Differential Equations with p-Laplacian. (14th November 2017) - Tian, Yuansheng; Sun, Sujing; Bai, Zhanbing
Abstract : The multiplicity of positive solution for a new class of four-point boundary value problem of fractional differential equations with p -Laplacian operator is investigated. By the use of the Leggett-Williams fixed-point theorem, the multiplicity results of positive solution are obtained. An example is given to illustrate the main results.